Generation and Construction of Professional Identity - San Ramon Gago, Sonsoles (Education Policy Analysis Archives, 2001)
It is my aim in this article to carry out a thorough examination of the basic elements, ideology and symbolic representations which constitute the identity of a generation of schoolmistresses belonging to a crucial period in Spanish history: that of the intermediate Francoism, during the process of modernization which took place at the end of the 1950s. The investigation is based on live testimonies of schoolmistresses between the ages of 65 and 70. First, I will point out the antecedents of the profession of schoolmistress in Spain and show how circumstances made her role gradually and increasingly more important. Then I will reveal what kinds of opposition and obstacles schoolmistresses came up against and had to overcome in order to obtain professional equality with male colleagues. Finally, I will contextualize and interpret, in cultural terms, the attitudes, images and motivations, which turned out to be very symbolic, that arose during the interviews with these women. This article, which fills a large gap in research on this subject, concentrates on a very particular and decisive moment. It is my intention to invite the reader to reflect on a social phenomenon of great importance today: that of the feminization of teaching, which can be seen in most countries and whose influence can be observed, not only in a country´s educational system, but in the economic, political, religious and cultural spheres as well.